Pengaruh Model Pembelajaran Kooperatif Student Teams Achievment Devision (STAD) dan Rasa Percaya Diri Siswa terhadap Hasil Belajar Matematika Siswa SMA - Giyanti Giyanti (GAUSS: Jurnal Pendidikan Matematika, 2018)
This study aims to determine the effect of learning model on the mathematics learning outcomes of the students, knowing the influence of students' self-confidence in the results of learning mathematics. Furthermore, to determine the effect of learning models and students' self-confidence altogether to the result of learning mathematics. The research used is experimental method. The samples used from the affordable population taken from 34 people as the sample of the test instrument, and 68 people as the research sample using proportional random sampling technique from all grade X on SMA Negeri 3 Kabupaten Tangerang. The data were collected by giving the result of learning tests and questionnaires. The data analysis consists of testing the research instrument of validity, reliability, difficulty index, and distinguishing power*. Furthermore, there are the test of requirement analysis through normality and homogeneity test. The hypothesis tested by ANOVA 2 Lanes and Tukey. This study was conducted on February to May, 2017. Based on the results of the hypothesis and data analysis, it is concluded that the following things are: 1) There is an influence between the learning model on the learning outcomes of mathematics. 2) There is an influence between students' self-confidence on mathematics learning outcomes. 3) There is an interaction effect between learning methods and students' self-confidence on mathematics learning outcomes.